(untitled) (Cardiovascular Journal, 2023)
Background: Rapid assessment of left ventricular ejection fraction (LVEF) may be critical among emergency department (ED) patients. This study examined the predictive relationship between bedside Left Ventricular Internal Dimension at End-Diastole and the Mitral Valve E-Point Septal Separation (EPSS) Ratio to the quantitative calculated LVEF. Methods: A prospective observational study was conducted on a sequential convenience sample of patients, receiving comprehensive Transthoracic Echocardiography (TTE). The current study recruited 100 patients who presented to the Cardiology Clinic of Lab Aid Cardiac Hospital. Echocardiographic examinations were performed to obtain 2D guided M-mode measurements of the LVIDd & EPSS in addition to calculation of conventional, quantitative LVEF. All the measurements were done in the Para-sternal long-axis view. Results: It was found that LVEF determined by EPSS has very significant negative correlation with Calculated LVEF (r=—.766, p<0.001). LVEF determined by LVIDd/EPSS has also very significant positive correlation with calculated LVEF (r=.806, p<0.001), but correlation of LVIDd/EPSS was significantly higher than correlation of LVEF with only EPSS. LVIDd/EPSS <7 is strongly predictive of reduced LVEF<50% (P<.001). An LVIDd/EPSS <6 mm is evidence of reduced LVEF < 40%, (P<.001). Of note LVIDd/ EPSS <4 mm correlates with severely decreased function, with an estimated LVEF of <30% (P <.001). As was shown by the results of the linear regression analysis, most significant determinant of LVEF was LVIDd/EPSS (R=.806, p<0.001) The results of the linear regression analysis indicated that the LVIDd/EPSS was an independent predictor of the LVEF (P<0.001). Measurements of LVIDd/EPSS were significantly associated with the calculated measurements of LVEF from comprehensive TTE. Conclusion: The LVIDd/EPSS may allow certain clinicians, especially beginners and emergency department physicians, to assess the LVEF when other methods are not available or questionable. Cardiovasc j 2023; 16(1): 24-31